PELANGGARAN TERHADAP PRINSIP KEHATI-HATIAN KREDIT DALAM PERSPEKTIF HUKUM PIDANA - Sofia Yunita; Ifrani Ifrani (Badamai Law Journal, 2020)
This research was conducted using research methods, namely, the type of normative legal research, problem approach using the Statute Approach and Conceptual Approach, the nature of this research is analytical descriptive, descriptive research type with primary huum sources, secondary legal materials and tertiary legal materials obtained through library research.         From the results of research and discussion of the issues raised at least some conclusions can be drawn. First, from the results of the elaboration of the, it can be seen that the actions of commissioners, directors and bank employees violate the precautionary principle (bank compliance) including Banking Crimes. Second, Credit Officers (Managers) are responsible for checking credit that has been decided in accordance with the principle of prudence, believe in the correctness of data and information in credit decisions, believe supporting documents for credit decisions are complete, valid, valid and legally binding, believing that analysis and evaluation credit has been done correctly. The Credit Administration is responsible for ensuring compliance with the Precautionary Principle by giving opinions.